2012
DOI: 10.1179/1743289811y.0000000035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BaSO4, CaCO3, kaolin and quartz fillers on mechanical, chemical and morphological properties of cast polyurethane

Abstract: For industrial applications of engineering polymers such as polyurethane, polyamides and polyesters, the addition of suitable reinforcing inorganic fillers is a practical and convenient method to achieve the desirable mechanical and chemical properties. In this study, the mechanical, chemical and morphological properties of cast polyurethane samples containing barium sulphate, calcium carbonate, kaolin and quartz fillers were investigated. In the formulation of these samples, the ranges of inorganic filler wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…1.2 mol L −1 , a reactant feed flow rate of 10.42 m s −1 , and an impingement angle of 60°. 19,20 A suspension of nano-barium sulfate of known solid content was poured into a fournecked flask. A constant temperature water bath was adjusted to the experimental temperature and heated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1.2 mol L −1 , a reactant feed flow rate of 10.42 m s −1 , and an impingement angle of 60°. 19,20 A suspension of nano-barium sulfate of known solid content was poured into a fournecked flask. A constant temperature water bath was adjusted to the experimental temperature and heated.…”
Section: Discussionmentioning
confidence: 99%
“…Nano-barium sulfate with particle size of 30 nm was prepared using an impingement flow reactor with a feed cross-sectional area of 1.56 mm 2 , a reactant concentration of 1.2 mol L −1 , a reactant feed flow rate of 10.42 m s −1 , and an impingement angle of 60°. 19,20 A suspension of nano-barium sulfate of known solid content was poured into a four-necked flask. A constant temperature water bath was adjusted to the experimental temperature and heated.…”
Section: Methodsmentioning
confidence: 99%
“…Morphological examination of the foam revealed that the cell geometry characteristics exert a significant influence on the observed mechanical characteristics. M. Shahzamani et al [16] proposes the the mechanical, chemical and morphological properties of cast polyurethane samples containing barium sulphate, Brazilian Journal of Development, Curitiba, v.10, n.1, p. 1605-1622, jan., 2024 calcium carbonate, kaolin and quartz fillers were investigated. And the results of mechanical property tests, such as tear resistance, tensile strength, elongation at break, hardness and abrasion resistance, were evaluated.…”
Section: Related Workmentioning
confidence: 99%
“…Most of them are iron-rich metal oxides (with prevailing Fe along with variable amounts of Zn, Cu, Cr, Mn, Ni; Figure A1), others are silicates (mainly mica and feldspar grains; Figure A1), while some granules consist of barium sulfate. All these particles are ascribed to the fillers used to regulate and improve rubber properties such as wet grip and rolling resistance of the tire treads (e.g., [34][35][36]). Rubber is the most widespread material within the MM line as the tire tread of the wheels of both the cabins and the braking system are made of rubber.…”
Section: As a Source Of Pmmentioning
confidence: 99%